Time-trial performance is not impaired in either competitive athletes or untrained individuals following a prolonged cognitive task - Clark, I. E.; Goulding, R. P.; Di Menna, F. J.; Bailey, S. J.; Jones, M. I.; Fulford, J.; McDonagh, S. T. J.; Jones, A. M.; Vanhatalo, A. (European Journal of Applied Physiology, 2019)
It has been reported that mental fatigue decreases exercise performance during high-intensity constant-work-rate exercise (CWR) and self-paced time trials (TT) in recreationally-trained individuals. The purpose of this study was to determine whether performance is impaired following a prolonged cognitive task in individuals trained for competitive sport. Ten trained competitive athletes (ATH) and ten untrained healthy men (UNT) completed a 6-min severe-intensity CWR followed by a 6-min cycling TT immediately following cognitive tasks designed to either perturb (Stroop colour-word task and N-back task; PCT) or maintain a neutral (documentary watching; CON) mental state. UNT had a higher heart rate (75 ± 9 v. 69 ± 7 bpm; P = 0.002) and a lower positive affect PANAS score (19.9 ± 7.5 v. 24.3 ± 4.6; P = 0.036) for PCT compared to CON. ATH showed no difference in heart rate, but had a higher negative affect score for PCT compared to CON (15.1 ± 3.7 v. 12.2 ± 2.7; P = 0.029). Pulmonary O2 uptake during CWR was not different between PCT and CON for ATH or UNT. Work completed during TT was not different between PCT and CON for ATH (PCT 103 ± 12 kJ; CON 102 ± 12 kJ; P > 0.05) or UNT (PCT 75 ± 11 kJ; CON 74 ± 12 kJ; P > 0.05). Compared to CON, during PCT, UNT showed unchanged psychological stress responses, whereas ATH demonstrated increased psychological stress responses. However, regardless of this distinction, exercise performance was not affected by PCT in either competitive athletes or untrained individuals.